A handful of sounds : cued articulation in practice - Passy, Jane (ACER Press, 2003)
The Cued Articulation (CA) system of hand cues and colour codes was devisedby speech pathologist, Jane Passy, to help severely speech-and language-disorderedchildren understand and pronounce the sounds of speech. A Handful of Sounds is a compilation of chapters written by enthusiastic users ofCued Articulation from Australia and the UK. Contributors communicate novelways in which to apply Cued Articulation, show how it can support other literacyschemes, and demonstrate how simple it is to learn and apply. A Handful of Soundsalso includes the following additional practical support ideas in the.